Different immune response of pigs to Mycobacterium avium subsp. avium and Mycobacterium avium subsp. hominissuis infection - Stepanova, Hana; Pavlova, Barbora; Stromerova, Nikola; Ondrackova, Petra; Stejskal, Karel; Slana, Iva; Zdrahal, Zbynek; Pavlik, Ivo; Faldyna, Martin (Veterinary microbiology, 2012)
Mycobacterium avium subsp. avium (MAA) and Mycobacterium avium subsp. hominissuis (MAH) are the most common mycobacterial species isolated from granulomatous lesions in swine in countries with controlled bovine tuberculosis. This study is focused on the immunological aspect of MAA and MAH infection in pigs. We detected induction of humoral and cell-mediated immunity in experimentally infected pigs. Specific antibodies were analyzed in serum by ELISA and the IFN-γ release assay was used for evaluation of cell-mediated immunity. While MAA induced a significant increase of both types of immune responses, MAH-infected pigs had an unvarying level of specific antibodies and showed low cell-mediated immunity with high individual variability. The subsequent in vitro experiment confirmed the lower immunogenicity of the MAH strain in comparison to MAA. MAH-infected porcine monocyte-derived macrophages showed a weaker induction of pro-inflammatory mediators in comparison to MAA, which included mRNA for IL-1β, TNF-α, IL-23p19, IL-18 and chemokines CCL-3, CCL-5, CXCL-8 and CXCL-10. Additionally, qualitative proteomic analysis revealed 28 proteins exclusively in MAA and 7 proteins unique to MAH. In conclusion, closely related M. avium subspecies MAA and MAH showed different capacities to stimulate the porcine immune system. From a diagnostic point of view, the IFN-γ release assay showed higher sensitivity than the detection of specific antibodies by ELISA and seems to be an effective tool for discrimination of MAA-infected pigs. In the case of MAH infection, the IFN-γ release assay could fail because of the low immunogenic capacity of the MAH strain.
Keywords: tuberkulóza; mediátory zánětu; buněčná imunita; prasata; Tuberculosis; Inflammation Mediators; makrofágy; Interleukin-23 Subunit p19; Tumor Necrosis Factor-alpha; Swine Diseases; Swine; Macrophages; interleukin-23 - podjednotka p19; zvířata; interleukin-18; Mycobacterium avium; nemoci prasat; Immunity, Cellular; Animals; Interleukin-18; TNF-alfa